The Effect of Temperature Cooking of Sugar Juice and Stirring Speed on The Quality of Brown Sugar Cane - Dewi, Shinta Rosalia; Agustiningrum, Dyah Ayu; Indriani, Dina Wahyu; Sugiarto, Yusron; Maharani, Dewi Maya; Yulianingsih, Rini; Izza, Ni'matul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Research of the effect of cooking temperature and stirring speed on the quality of brown sugar cane were processed by vacuum vertical evaporator have been done. Brown sugar cane produced from purified green cane juice. The purification was done with addition of Ca(OH)2. Pure juice cooked with cooking temperature of 60, 70, and 80 oC, and the stirring speed of 200 and 250 rpm. Brown sugar cane was analyzed for color, moisture content, ash content, sucrose, and organoleptic test (hedonic quality test for color, flavor, and texture of hardness). The results showed that the higher of cooking temperature, the better the quality of color, flavor, and hardness brown sugar cane produced. While the higher stirring speed, lower moisture content of brown sugar, so the hardness of brown sugar was better. Besides effect of cooking temperature and stirring speed, quality of brown sugar cane was affected by the quality of cane juice and juice purification process. Good quality of cane juice will produce high yield, low moisture content, high sucrose, and good color, flavor, and hardness. The best result was obtained on brown sugar cane produced by cooking temperature of 70 oC and stirring speed of 250 rpm, which was obtained yield of 8.23%, sucrose of 75.37%, hardness of 4.52 kg/cm2, bright and high color intensity of brown sugar cane.Keywords: cane sugar, vacuum evaporator, brown sugar, stirring, cooking temperature